2006
DOI: 10.1021/jm0502900
|View full text |Cite
|
Sign up to set email alerts
|

Are Target-Family-Privileged Substructures Truly Privileged?

Abstract: One of the early and effective approaches to G-coupled protein receptor target family library design was the analysis of a set of ligands for frequently occurring chemical moieties or substructures. Various methods ranging from frameworks analysis to pharmacophores have been employed to find these so-called target-family-privileged substructures. Although the use of these substructures is common practice in combinatorial library design and has produced leads, the methods used for finding them rarely verified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
86
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 26 publications
1
86
0
2
Order By: Relevance
“…These substructures are often used to build up target familyselective screening libraries. Schnur et al performed a substructure analysis of ligand sets from five different target families and examined the occurrence of potential privileged substructures [19]. They found a remarkable promiscuity of the substructures and concluded that most of these substructures might be better described as drug-like and not as target family specific.…”
Section: Introductionmentioning
confidence: 99%
“…These substructures are often used to build up target familyselective screening libraries. Schnur et al performed a substructure analysis of ligand sets from five different target families and examined the occurrence of potential privileged substructures [19]. They found a remarkable promiscuity of the substructures and concluded that most of these substructures might be better described as drug-like and not as target family specific.…”
Section: Introductionmentioning
confidence: 99%
“…In many instances, substructures considered to be target class-selective on the basis of frequency of occurrence analysis have also been detected in compounds active against other target families; 2 hence, the existence of truly privileged structural motifs has been controversial. 2 Recently, we have carried out a large-scale analysis of public domain compound data to investigate whether target class-selective molecular scaffolds exist.…”
mentioning
confidence: 99%
“…In many instances, substructures considered to be target class-selective on the basis of frequency of occurrence analysis have also been detected in compounds active against other target families; 2 hence, the existence of truly privileged structural motifs has been controversial. 2 Recently, we have carried out a large-scale analysis of public domain compound data to investigate whether target class-selective molecular scaffolds exist. 3 To avoid potential caveats of occurrence frequency-based analysis, we searched for compounds with multiple activity annotations and formed pairs of biological targets that were "connected" by at least five active compounds.…”
mentioning
confidence: 99%
“…9 As tecnologias vigentes, no entanto, proporcionam metodologias avaliativas baseadas em bibliotecas oriundas de química combinatória, o que implica na identificação precoce de fragmentos estruturais que poderiam resultar na promiscuidade de protótipos. 27 Esses fragmentos, porém, sob outra perspectiva, receberam a original denominação de "estrutura privilegiada", termo formulado por Evans e Patchett, que corresponde à estrutura mínima presente em diversos compostos protótipos de fármacos capazes de interagir com mais de um tipo de biorreceptor. 4,28,29 Este conceito tomou um significado além da original concepção de Evans, ao ser correlacionado a uma estrutura mínima seletiva para uma família de receptores.…”
Section: Estruturas Privilegiadasunclassified
“…4,28,29 Este conceito tomou um significado além da original concepção de Evans, ao ser correlacionado a uma estrutura mínima seletiva para uma família de receptores. 27 Entretanto, a identificação de uma estrutura privilegiada consiste em um grande desafio e não pode estar simplesmente correlacionada à frequência de ocorrência de certas subunidades em coleções de moléculas bioativas, pois necessitam de estudos criteriosos que confirmem a importância das subunidades para interação fármaco-receptor. 27 Não obstante, a seletividade de um fragmento por uma família de receptores não é de fácil atribuição, o que ressalta a importância do desenho sob medida de moléculas para a determinação de estruturas privilegiadas segundo avaliações das relações estruturaatividade.…”
Section: Estruturas Privilegiadasunclassified